Phosphite‐Catalyzed C−H Allylation of Azaarenes via an Enantioselective [2, 3]‐Aza‐Wittig Rearrangement. Issue 40 (29th August 2019) - Motaleb, Abdul; Rani, Soniya; Das, Tamal; Gonnade, Rajesh G.; Maity, Pradip
Abstract: A phosphite‐mediated [2, 3]‐aza‐Wittig rearrangement has been developed for the regio‐ and enantioselective allylic alkylation of six‐membered heteroaromatic compounds (azaarenes). The nucleophilic phosphite adducts of N‐allyl salts undergo a stereoselective base‐mediated aza‐Wittig rearrangement and dissociation of the chiral phosphite for overall C−H functionalization of azaarenes. This method provides efficient access to tertiary and quaternary chiral centers in isoquinoline, quinoline, and pyridine systems, tolerating a broad variety of substituents on both the allyl part and azaarenes. Catalysis with chiral phosphites is also demonstrated with synthetically useful yields and enantioselectivities. Abstract : Powered by rearomatization : The adduct of a nucleophilic chiral phosphite with an azaarene N‐allyl salt undergoes a stereoselective base‐mediated aza‐Wittig rearrangement. This method efficiently generates tertiary and quaternary chiral centers in isoquinoline, quinoline, and pyridine systems along with an alkene handle for further functionalization.